Body growth, upper arm fat area, and clinical parameters in children with nephropathic cystinosis compared with other pediatric chronic kidney disease entities. Issue 2 (14th January 2022) - Kluck, Rika; Müller, Sophia; Jagodzinski, Celina; Hohenfellner, Katharina; Büscher, Anja; Kemper, Markus J.; Oh, Jun; Billing, Heiko; Thumfart, Julia; Weber, Lutz T.; Acham‐Roschitz, Birgit; Arbeiter, Klaus; et al.
Abstract: Children with infantile nephropathic cystinosis (INC), an inherited lysosomal storage disease resulting in cystine accumulation in all body cells, are prone to progressive chronic kidney disease (CKD), impaired growth and reduced weight gain; however, systematic anthropometric analyses are lacking. In this prospective multicenter study we investigated linear growth, body proportion, body mass index (BMI), upper arm fat area (UFA) and biochemical parameters in 43 pediatric INC patients with CKD stages 1 to 5 and 49 age‐matched CKD controls, with 193 annual measurements. INC patients showed more impaired height than CKD controls (−1.8 vs −0.7 z ‐score; P  < .001), despite adequate cysteamine therapy, treatment for Fanconi syndrome and more frequent use of growth hormone. Only the youngest INC patients shared the same body pattern with CKD controls characterized by preferential impairment of leg length and rather preserved trunk length. In late‐prepuberty, body pattern changed only in INC patients due to improved leg growth and more impaired trunk length. Mean UFA z ‐score in INC patients was slightly reduced in early childhood and progressively decreased thereafter reaching −0.8 z ‐score in adolescence, while CKD controls showed a steady increase in standardized BMI and UFA especially during adolescent age. Menarche in female INC patients was significantly delayed compared to CKD controls. Our data indicate that with age and progression of disease, pediatric INC patients undergo unique changes of body growth and fat stores that are distinct from those with CKD stemming from other causes, suggesting other factors apart from CKD to contribute to this development. Pediatric patients with infantile nephropathic cystinosis display more severe impaired linear growth than other peer CKD patients, despite of cysteamine treatment, supplementation for Fanconi syndrome, and more frequent use of growth hormone, with a distinct change of body proportions and overall lower body fat.